O sentido da noção de sublimação na filosofia de Schopenhauer - Fonseca, Eduardo Ribeiro da (2010)
Freud thinks sublimation ("Sublimierung") as a modification of actions and objects of satisfaction ("Befriedigung") of sexual impulses, caused by the difference between the degree of pressure of desire and the possibilities of direct satisfaction. The difference between one thing and another, results from the factor that drives the impulses toward their destinations desexualized. These forms enable improvement of language and of cultural production that result in the civilizing process, capitalizing on the forces of sexuality and redirecting to target socially productive. Therefore, all human activity is always sexualized to some degree and seeks satisfaction. But in Schopenhauer’s case occurs the same? The philosopher of the Will uses two different words: sublimation ("Sublimierung"), which accounts for a conversion process of beautification and subtilization representations, although not made any systematic attempt to directly target impulse. This notion is complemented by the concept of the sublime ("Erhabenen") present especially in the Metaphysics of the Beautiful ("Metaphysik des Schönen"), which characterizes the man as "dark and stormy impetus of wanting", which has the polarity "of the genitals as their focus," and while the contrast polarity of the brain, which in the language of the philosopher is the "eternal subject, free, serene and pure knowledge."